A Multi‐signal Fluorescent Probe with Multiple Binding Sites for Simultaneous Sensing of Cysteine, Homocysteine, and Glutathione. Issue 18 (23rd March 2018) - Yin, Guo‐xing; Niu, Ting‐ting; Gan, Ya‐bing; Yu, Ting; Yin, Peng; Chen, Hai‐min; Zhang, You‐yu; Li, Hai‐tao; Yao, Shou‐zhuo
Abstract: A novel fluorescent probe was developed by integrating chlorinated coumarin and benzothiazolylacetonitrile and exploited for simultaneous detection of cysteine (Cys), homocysteine (Hcy), and glutathione (GSH). Featuring four binding sites and different reaction mechanisms for different biothiols, this probe exhibited rapid fluorescence turn‐on for distinguishing Cys, Hcy, and GSH with 108‐, 128‐, 30‐fold fluorescence increases at 457, 559, 529 nm, respectively, across different excitation wavelengths. Furthermore, the probe was successfully applied to the fluorescence imaging of endogenous Cys and GSH and exogenous Cys, Hcy, and GSH in living cells. Abstract : All together now : A novel fluorescent probe was developed for simultaneous sensing of cysteine (Cys), homocysteine (Hcy), and glutathione (GSH). Featuring four binding sites and different reaction mechanisms for different biothiols, this probe exhibited rapid fluorescence turn‐on for distinguishing Cys, Hcy, and GSH. The probe was successfully applied to the fluorescence imaging of endogenous Cys and GSH and exogenous Cys, Hcy, and GSH in living cells.